PENGGUNAAN MEDIA AUGMENTED REALITY (AR) UNTUK MENINGKATKAN KETERAMPILAN GERAK TARI TORTOR SISWA KELAS V SDN 028 TAPUI INDAH (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The motor skills of fifth-grade students in performing the Tor-Tor dance are still relatively low, particularly in terms of movement accuracy and coordination. This condition indicates that the learning process has not yet provided clear visual examples to help students understand the required techniques. This study aims to improve students’ dance performance skills through the use of Augmented Reality (AR), which presents interactive and easily observable movement models. This research employed a Classroom Action Research (CAR) method conducted in two cycles involving 29 students. Each cycle consisted of planning, action implementation, observation, and reflection stages. Data were collected through observation and performance assessments and analyzed descriptively. The findings reveal a significant improvement after the use of AR media. In the pre-cycle stage, the average student score was 47.17, categorized as low. After the first cycle, the average score increased to 67.23. A further increase occurred in the second cycle, with an average score of 87.64, categorized as very good. In addition to improved scores, students demonstrated higher confidence and enthusiasm in performing the dance movements.These results indicate that AR media is effective in enhancing dance learning, as it provides concrete, engaging, and easily followed visual demonstrations of movement techniques.